Contrastive Discourse Analysis. Functional and Corpus Perspectives - Rodríguez Arrizabalaga, Beatriz (Miscelánea: A Journal of English and American Studies, 2015)
M. Taboada, S. Doval Suárez and E. González Álvarez Sheffield: Equinox, 2013